Влияние цинка на биологическую ценность грибного препарата - Супрун, С.М.; Донченко, Г.В.; Пархоменко, Ю.М.; Харкевич, Е.С.; Аретинская, Т.Б.; Курченко, И.Н.; Cтепаненко, С.П.; Кучмеровская, Т.М. (Фактори експериментальної еволюції організмів, 2015)
Aims. Obtaining and investigation of zinc-containing preparation on the basis of selected strains of micromycetes. Methods. New methodical technique consisting in adding of zinc aquachelate in cultivation medium to obtain the enriched product was used. Results. The obtaining protein-vitamin preparations had a wide range of natural biologically active substances: polyunsaturated fatty acids, B group vitamins and their derivatives. The study of hemolymph corpuscles haemocytes indicated stimulation of nonspecific immunity of insects, improving their survival. Conclusions. It was established that the addition of zinc aquachelate to the culture medium promoted to improve the biological value of fungal additive. The studies confirmed the prospectivity of using these additives to enhance production indicators and natural resistance of animals. Keywords: vitamin, protein, aminoacid, fatty acid, fungal preparation.